Characterisation of the Osteoclastogenic Potential of Human Osteoblastic and Fibroblastic Conditioned Media - João Costa-Rodrigues (2010)
Although M-CSF and RANKL are sufficient to promote in vitro osteoclastogenesis, in vivo this is a complex process which requires the action of many signalling molecules and cellular crosstalks. In this work, isolated or combined Conditioned media, obtained from human adult skin fibroblast and bone marrow cells, were tested for their osteoclastogenic potential, through an indirect co-culture system, in the absence of recombinant M-CSF and RANKL Osteoclastogenesis was assessed on human peripheral blood mononuclear cells (PBMC) and CD14+ cell cultures by quantification of total protein content, tartrate-resist ant acid phosphatase (TRAP) activity, presence of multinucleated cells positive for TRAP, RT-PCR of TRAP, CATK, CA2, c-myc and c-src and presence of multinucleated cells displaying actin rings, vitronectin and calcitonin receptors. Cultures supplemented with M-CSF and RANKL were used as positive controls. It was observed that the Conditioned medium from dexamethasone osteogenic-induced bone marrow cell cultures displayed the highest osteoclastogenic potential, with similar behaviour to that observed in the presence of both M-CSF and RANK-L. Comparatively, fibroblastic Conditioned medium elicited a slightly lower osteoclastogenic response. Combination of both Conditioned media resulted in a significant increase of TRAP activity. Oil the other hand, Conditioned medium from non-osteogenic-induced bone marrow Cell Cultures presented the lowest osteoclastogenic potential. These results were observed for both PBMC and CD14+ cell Cultures, Suggesting that fibroblast and osteoblast cells are able to modulate osteoclastogenesis in the absence of physical cell-cell interactions. In addition, osteoclastogenic potential of bone marrow cells increases with their osteoblastic differentiation. J. Cell. Biochem. 109: 205-216, 2010. (C) 2009 Wiley-Liss, Inc.